Gadget Addiction: Opioid of the Era? - Zakaria, Rozanizam (International Journal of Human and Health Sciences (IJHHS), 2019)
Technology has certainly helped human race to advance forward and created the informa t ion revolution. Gadgets armed with internet have transformed our lives in many ways and shifted our paradigm regarding human relationship, works and life in general in this era of instant gratification. While technology has nurtured the human race, questions raise regarding the limit in which these two are interconnected. Does this advancement simplify life or actually make it more complex? As per suggested by the Hooked Theory, business model of internet, social medial and digital applications revolve around satisfying human needs, targeting our very own brain reward circuit. This has created concerns among sociologists, psychiatrists and psychologists regarding the potential rise of ‘new opioid’ for the era – the gadgets. We will discuss range of epidemiological data to visualize the severity of the situation and highlights different views on the concept of gadget addiction. This includes understanding the difficult y in coming to term regarding whether our over-attachment to gadget is a form behavioura l addiction or merely a transient social trend. From Hikikomori phenomenon to cyber-induced depression, the topic will also elaborate various impacts of gadget addiction, primarily on mental and psychological health, interpersonal relationship and human behavior. In particular, the focus will be on the impact of gadget addiction towards vulnerable groups, especially children and adolescents. The discussion will also integrate various practical holistic solutions to the problem without denying the integral role that technology has in our life. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 24